Development and Use of Gene Therapy Orphan Drugs—Ethical Needs for a Broader Cooperation Between the Pharmaceutical Industry and Society - Kerpel-Fronius, Sandor; Baroutsou, Varvara; Becker, Sander; Carlesi, Roberto; Collia, Luis; Franke-Bray, Brigitte; Kleist, Peter; Kurihara, Chieko; Laranjeira, Luis Filipe; Matsuyama, Kotone; Naseem, Shehla; Schenk, Johanna; et al. (Frontiers in Medicine, 2020)
Gene therapy orphan medicinal products constitute a unique group of new drugs which in case of hereditary diseases are usually administered only once at an early age, in the hope to provide sufficient gene product to last for the entire life of the patients. The combination of an exceptionally large single payment and the life-long clinical follow-up needed for understanding the long-term benefits and safety of gene therapy, represent new types of scientific, financial, social and ethical challenges for the pharmaceutical industry, regulators and society. With special consideration of the uniqueness and importance of gene therapy, the authors propose a three points plan for a close cooperation between the pharmaceutical industry and society to develop orphan gene therapy. (1) In fully transparent health technology negotiations a close and long-lasting, contractually fixed cooperation should be established between the manufacturers and local health-care stakeholders for sharing the medical and scientific benefits, the financial risks as well as the burdens of the post-authorization clinical and regulatory development. (2) The parties should agree on a fair, locally affordable drug price without the usually very high premium price calculated to compensate for the low number of patients. In case of high manufacturing costs, the companies should offer prolonged, 15–20 years long payment by installment with risk-sharing, especially considering that the late outcome of the treatment is unknown. Society should assist scientifically and financially organizing a specific patient registry, treatment in specialized hospitals and adequate long-term follow-up of patients, the coordinated management of financial transactions related to the risk sharing program. (3) The post-authorization treatment and prolonged observation of additional new cases coordinated by society should provide real world data needed for the modern complex regulatory evaluation of gene therapy products by the competent authorities. We assume that fair sharing of the benefits and risks as well as a well-organized cooperation of society with the industry in collecting real world evidence might result in better drug evaluation and improved accessibility due to lower prices. The outlined concept might support gene therapy more efficiently than the presently requested outstandingly high prices.